Heterogeneous Nuclear Ribonucleoprotein B1 Expressed in Esophageal Squamous Cell Carcinomas as a New Biomarker for Diagnosis - Matsuyama, Satoru (Jpn J Cancer Res, 2000)
We recently reported that heterogeneous nuclear ribonucleoprotein (hnRNP) B1 was overexpressed in most human lung cancers, especially squamous cell carcinoma (SCC), as well as human oral SCC. To find the significance of hnRNP B1 in cancer diagnosis, we studied hnRNP B1 expression in 16 paraffinized sections of esophageal SCC, using immunohistochemical staining with antihnRNP B1 polyclonal antibody, raised in a rabbit. We compared the expression of hnRNP B1 in cancerous and noncancerous regions of the same specimen: enhanced expression was observed in 63% of cancerous regions (10/16), whereas none of the noncancerous regions showed enhanced expression. The enhanced expression of hnRNP B1 in cancerous regions was compared with that in noncancerous tissue in relation to histopathological grade: 83% for well differentiated (5/6), 83% for moderately differentiated (5/6) and 0% for poorly differentiated (0/4). Histologically, enhanced expression of hnRNP B1 was observed around cancer pearls, as well as in the cells of nests lacking keratinization in well and moderately differentiated SCC. Western blotting analysis revealed enhanced expression in three frozen specimens of moderately differentiated SCC. Using esophageal cancer cell lines, we further confirmed the decreased expression in poorly differentiated SCC cells, compared with other differentiation types. All our results support the significance of hnRNP B1 expression in esophageal SCC as a unique diagnostic marker with regard to association between expression level and histopathological grading.